Dinamika Perilaku Merokok Pada Remaja - Mulyani, Tri; , Dr. Sri Lestari, S.Psi.,M.Si (2015)
The phenomenon of smoking behavior in adolescents now increasingly alarming and it has become a trend among both junior high school and senior high school students; even some elementary school students also have shown the smoking behavior. This research aims are to discover an experience and describe the dynamics of smoking behavior in adolescents who carried out on 78 students, consists of eight elementary school students, 40 of junior high school students and 30 of high school students. The research uses a method of qualitative by approaching a phenomenology method. Data was gathered using an open-questionnaire and semi-structured interview. Data analysis was done with the analysis and descriptive thematic. The results of research is smoking behavior in adolescents was found since 10 years old even some seven years old. Smoking behavior was done by the guys on the road, cafe, hang out place, mosque, and sometimes at school. The first experience smoking tasted bitter, coughing, dizzy and nausea, but there is still a desire to try again because they felt fun together with friends. The next experience the body feels fresh, fit, warm and comfortable when smoking. Beside it also gives a sense of calm, relaxed, spirit and give the impression of more adult, male, macho, prestige and raised in the group were brought up. The research also reveals behind a feeling above are the teenagers also feel sorry, afraid, and anxious for the results of caused by smoking. The health effect was already felt often asphyxiate, dizzy, chest pain and so weak. In terms of learning also feel disturbed, less concentration and tired quickly, even though there is who became a spirit (13, 33 %) at high school students.